2023
DOI: 10.1093/hmg/ddad159
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of common genetic risk factors between thyroid traits and breast cancer

Elise A Lucotte,
Yazdan Asgari,
Pierre-Emmanuel Sugier
et al.

Abstract: Breast cancer (bc) risk is suspected to be linked to thyroid disorders, however observational studies exploring the association between bc and thyroid disorders gave conflicting results. We proposed an alternative approach by investigating the shared genetic risk factors between bc and several thyroid traits. We report a positive genetic correlation between bc and thyroxine (FT4) levels (corr = 0.13, p-value = 2.0x10−4) and a negative genetic correlation between bc and thyroid-stimulating hormone (TSH) levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 63 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…Primary hypothyroidism will inevitably lead to an increase in TSH. TSH promotes the development of thyroid cancer ( 28 ), while a recent study found a negative genetic correlation between TSH levels and breast cancer ( 29 ), however, its effect on gastric cancer directly or indirectly is unknown. More research is needed to target certain gene regions downstream (such as key enzymes, metabolites, and signaling, transporters and receptor proteins) to develop preventive strategies and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Primary hypothyroidism will inevitably lead to an increase in TSH. TSH promotes the development of thyroid cancer ( 28 ), while a recent study found a negative genetic correlation between TSH levels and breast cancer ( 29 ), however, its effect on gastric cancer directly or indirectly is unknown. More research is needed to target certain gene regions downstream (such as key enzymes, metabolites, and signaling, transporters and receptor proteins) to develop preventive strategies and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…development of thyroid cancer (28), while a recent study found a negative genetic correlation between TSH levels and breast cancer (29), however, its effect on gastric cancer directly or indirectly is unknown. More research is needed to target certain gene regions downstream (such as key enzymes, metabolites, and signaling, transporters and receptor proteins) to develop preventive strategies and treatments.…”
mentioning
confidence: 99%
“…development of thyroid cancer (28), while a recent study found a negative genetic correlation between TSH levels and breast cancer (29), however, its effect on gastric cancer directly or indirectly is unknown. More research is needed to target certain gene regions downstream (such as key enzymes, metabolites, and signaling, transporters and receptor proteins) to develop preventive strategies and treatments.…”
mentioning
confidence: 99%